Dolutegravir, Second Generation Integrase Inhibitor: A New Hope for HIV Patient. Issue 1 (16th May 2018) - Yadav, Geeta; Kumar, Piyush; Kumar, Yugal; Singh, Pradeep Kumar
Undeterred efforts are reported and still continue in future to achieve the goals of virologic suppression in HIV-infected individuals. Dolutegravir is the result of all the efforts made in this direction. It is a recent integrase inhibitor drug approved by the US FDA (Food and Drug Administration) for use in the treatment-naïve and treatment-experienced HIV-infected patients. This article has reviewed all the aspects of the drug, including the structural and functional analyses, in vitro activity, pharmacokinetics, drug-drug interactions, MOA, metabolism, excretion, dosing/adverse effects and resistance profile. Dolutegravir is a potent and well tolerated antiretroviral agent that can play an important role in the treating patients harboring resistance to other antiretrovirals. Some new combinations of drug with other antiretrovirals are also in the pipeline that can increase the immunologic response of the HIV patients.